Estimating Willingness to Pay for Safe Beef - SARAITHONG, Wuthiya (Journal of Environmental Management and Tourism, 2016)
Consumers’ willingness to pay a premium price for safe and officially certified beef is analyzed in order to provide insights for producers, consumers, and the government. The analysis uses data from interviews in Bangkok, Thailand, with 620 respondents, who have experiences in buying beef. This study employs single- and double-bounded dichotomous choice contingent valuation method. The final model shows that only three variables are statistically significant in determining willingness to pay and used for the willingness to pay estimation. The weighted mean willingness to pay for safe and certified beef of Thai consumers is calculated to reflect the buying intention of both consumers with positive willingness to pay and those with true zero bids, and equal to 35.72 baht/kilogram or about 12% over the current market price of normal beef. This study’s finding could help producers decide whether to invest and raise the standard of their beef production, and in due course, improve people’s welfare in general.
Keywords: beef safety; willingness to pay; contingent valuation method